POLA PEMANFAATAN PELAYANAN KESEHATAN DAERAH TERTINGGAL, PERBATASAN, KEPULAUAN, DAN TERPENCIL (DTPK-T) DI INDONESIA (ANALISIS DATA RISKESDAS 2013) - Sri Wiyanti; Hari Kusnanto; Mubasysyir Hasanbasri (Jurnal Manajemen Pelayanan Kesehatan (The Indonesian Journal of Health Service Management), 2021)
Background: Utilization of health services is an important element in determining the health status of the community. Information on the utilization of health services are needed by health services management, in taking appropriate policy (Feldstein 1988). communities disadvantaged areas, islands, and remote border (DTPK-T) have limitations in the use of health services, this is due to geographical conditions that are difficult to reach, limited infrastructure and health human resources that add to the complexity of the problem. Objectives: Reviewing and analyzing the patterns of utilization of health services for people in underdeveloped regions, border, island, and remote. Method: This study uses secondary data from the Basic Health Research (RISKESDAS) in 2013, with a cross-sectional design. In this study focused to see the pattern of utilization of the public in disadvantaged areas, border, island, and remote in obtaining health services at the health center. Results: Least developed society, border, island, and remote use more health centers, out of total 42.623 respondents, approximately 18.882 people or 43.5% are utilizing the services health centers, physician practices 19.5%, gender, economic status, education, travel time and transportation costs, doctor’s diagnosis of the disease in the suffering of both communicable and non-communicable, rural location had a significant effect on health care utilization, while the category of regions did not have a significant effect on the utilization of health centers. Conclusion: People in, Less developed, border, island, and remote areas (DTPK-T) have made use of basic health care facilities (health centers), in addressing health issues. Special policies are needed in order to improve the quality of care by providing health resources, infrastructure, and availability of drugs.